Interaction of Personal and Social Positioning in the Formation of the Dialogical Self: A Study of Australian Adults - Raggatt, Peter (Studia Psychologica: Theoria et praxis, 2008)
Positioning theory, popular in the analysis of discourse, has been invoked to account for the dynamics of conflict in a dialogical self. It is argued that conflicting I-positions may have origins ”inside” in terms of personal dynamic conflicts (e.g., over esteem, agency, or communion needs), and ”outside” in terms of social constructions (e.g., arising from role conflicts and from embedding in power and status hierarchies). The paper reports findings from a study of positioning that demonstrates interactions between personal and social positioning in the formation of the dialogical self. Gender differences in positioning are also examined. It is concluded that the self embodies the personal and the social simultaneously, and that to reduce the self to pure ”social construction”, or its reverse, an echoing, self-contained reflexivity, is to commit to a reductionist agenda that may ultimately limit inquiry.